Optimizing Regional Governance in Batam City Government-Business Entity Institutional Dualism - Respationo, Soerya; Thapa, Nar Yan (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The development of special areas of Batam began in the 1970s. With the support of special regulations made by the central government, Batam City becomes a competitive place for investment in Indonesia. Moreover Batam has geographical advantage because of its strategic location and adjacent to Malaysia and Singapore.Purposes of the Research: The research examines the legal framework governing the relationship between the Batam City Government and Batam Concession Agency, identifying overlap and potential conflicts, and promoting synergy with the Batam Business Entity.Methods of the Research: The study approach employed. Secondary data is used in this normative legal research strategy.Results of the Research: Research suggests that the legal structure between Batam City Government and Batam Concession Agency should promote cooperation and collaboration. In practice, overlapping jurisdiction areas might leave unclear and confusing duties and responsibilities for each entity. They were fulfilling each entity's duties. Overlapping zones can interfere with development and public services and cause institutional conflicts. The legal framework may require clarity or amendment to improve the interaction between the Batam City Government and the Batam Concession Agency. Optimize local government, for optimal local government, the law must assist the Batam City Government, and Batam Concession Agency cooperate. Batam City and Batam Concession Agency labor together cooperatively. Batam City and Batam Concession Agency collaborate.